Determinan Beta Saham Perusahaan Real Estate dan Property di Bei - Jazuli, A Muhamad; Witiastuti, Rini Setyo (Management Analysis Journal, 2016)
This research aim to determine the effect of debt to equity ratio, current ratio, asset growth and return on equity on beta. Population in this research are all real estate and property companies listed in Indonesian Stock Exchange in 2012-2013 as many as 50 companies. The method used is purposive sampling , with 34 companies are selected with 50 samples on annual report are observed. Analysis technique that used here is multiple regression analysis using IBM SPSS Statistics 21. The result shows that debt to equity ratio has a negative non-significant effect, current ratio and return on equity has a positive significant and asset growth has a negative significant on beta. Suggestion for next research are add another fumdamental factors and add company categories.